Instilling Religious Moral Values in Storytelling Methods during the Covid 19 Pandemic Alkhairaat Kindergarten Taipa Palu City - Nurhayati .; Ika Rahmawati (Universitas Muhammadiyah Ponorogo, 2021)
The problem in this research is the instilling of religious moral values that have not developed as expected. The purpose of this research was to determine the effect of the storytelling method on the religious moral values of children in group B of Al- Khairaat Taipa Kindergarten, Palu City. This research used quantitative method with an experimental research type. The research subjects were 14 children. Collecting data were carried out through observation sheets and documentation. The technique of data collection was done by using percentage technique and t test. It was obtained from the results of descriptive analysis research, the average value of children's religious morals, there were 35.71% in the VWD category, 46.43% in the DE category, 12.50% in the SD category, and 5.36% in the U category. Meanwhile, the results of the research from the t-test showed that the t-count value was -14.877 with a significant 0.000, because of sig 0.05. Thus, it can be explained that H0 was rejected and H1 was accepted. Therefore, it can be concluded that the storytelling method has a significant effect on children's religious morals.